AB0226 Decline in anti-ccp and rheumatoid factor levels in patients with early rheumatoid arthritis after 2 years of treatment with intensive combination strategies, including prednisolone: the cobra-light trial. (12th June 2018) - Folmo, H.D.; ter Wee, M.M.; den Uyl, D.; Konijn, N.P.; Kerstens, P.J.; Voskuyl, A.E.; van Schaardenburg, D.; Nurmohamed, M.T.; Boers, M.; Lems, W.F.
Abstract : Background: Previous studies have proven that the COBRA-light strategy has similar effectiveness and safety as the COBRA strategy in treating early rheumatoid arthritis (RA) patients 1, 2 . However, the effect of these strategies on anti-cyclic citrullinated peptide (anti-CCP) and rheumatoid factor (RF) levels remains contradictory. Objectives: To investigate whether levels of anti-CCP and RF have changed after 2 years of treatment with COBRA or COBRA-light strategy. Methods: A total of 162 early RA patients were included in a randomised, open-label, multicenter trial and treated with either COBRA or COBRA-light strategy. After 1 year, the treatment protocol ended, and physicians continued treatment according to clinical judgment, aiming at clinical remission. Log-transformation was first performed before running any analyses in case of skewed distribution, and analyses were performed with Generalised Estimated Equations to evaluate the association between the medication strategies and the change of LN anti-CCP and LN RF levels on average over time. Results: Over 2 years' time, median anti-CCP and RF levels decreased significantly in COBRA (6%, and 24% respectively) and COBRA-light (4%, and 13%, respectively; table 1). Of the 102 anti-CCP positive patients at baseline, 10 (10%) became anti-CPP negative during treatment (5 COBRA vs. 5 COBRA-light). No significant difference between the two treatment strategies on the change of anti-CCP and RF levels over 2 years' time was found. Additionally, a significant association between baseline DAS44 and remaining anti-CCP positive over time was found (OR=1.8; 95% CI: 1.2–2.8). Conclusions: Both COBRA and COBRA-light strategies lead to substantial decreases in anti-CCP and RF levels over 2 years of treatment. Patients with a higher DAS44 at baseline have higher odds of being anti-CCP positive over 2 years' time. References: [1] ter Wee MM. Ann Rheum Dis. 2015;74(6):1233–1240. doi:10.1136/annrheumdis-2013-205143 [2] den Uyl D. Ann Rheum Dis. 2014;73(6):1071–1078. doi:10.1136/annrheumdis-2012-202818 Disclosure of Interest: None declared